Perancangan Alat Latihan Tinju Pengukur Jumlah Pukulan dan Kekuatan Pukulan Berbasis Internet of Things (IoT) - Alliya, Annisa Ul; Lindawati, Lindawati; Susanti, Eka (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Maintaining physical health is crucial, and one way to achieve this is through regular exercise. Boxing is a suitable choice as it not only helps maintain fitness but also serves as self-defense, relying on punching skills. Previously, a device was developed to measure kick strength, but its results were only accessible via a localhost web interface, limiting access from other devices. This study aims to design a device for measuring the quantity and strength of punches in boxing, accessible anywhere via the internet. The device utilizes piezoelectric sensors with a web interface for measurement. In addition to piezoelectric sensors, it incorporates Arduino Mega, LCD, and ESP32. Sensor accuracy testing showed an average error rate 5.09% and 0% data transmission failure. Over 60 seconds in 30 trials, an average of 90 punches were recorded with an average punch strength of 800.